'These Intimate Little Places': Cinema-Going and Public Emotion in Bolton, 1930-1954. (8th August 2019) - Jones, James
ABSTRACT: Building upon the methodological approach offered by the history of emotions, this article re-examines the records of Mass Observation's Worktown to explore how cinemas in Bolton functioned as sites of public emotion between 1930 and 1954. It suggests that the cinema was a unique emotional space in which tensions between the public and private nature of feeling were contested and developed. This article argues that Bolton's cinemas were instrumental not only in the leisure landscape of the town but also in the development of wider emotional practices (both individual and collective) in the mid-twentieth century.